Pengaruh Kompensasi dan Work-life Balance terhadap Turnover Intention pada PT. Maha Perkasa Indonesia Surabaya - Fitri Cahyaningrum; Hesty Prima Rini (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2026)
This study aims to analyze the impact of compensation and work–life balance on employees’ turnover intention at the well-established company PT. Maha Perkasa Indonesia. Data were collected through a questionnaire using a Likert scale, distributed via the Google Forms platform, and involved 43 active employees of PT. Maha Perkasa Indonesia as respondents. The study employed a quantitative approach, with data analysis conducted through several stages, including validity testing, reliability testing, R-square analysis, path analysis, and hypothesis testing. The results indicate that compensation has a significant effect on turnover intention. Based on these findings, the company is expected to be more proactive in managing its employees in order to reduce turnover intention.